2019
DOI: 10.1186/s12968-019-0532-9
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated quantification of biventricular volumes and function in cardiovascular magnetic resonance: applicability to clinical routine settings

Abstract: Background: Cardiovascular magnetic resonance (CMR) represents the clinical gold standard for the assessment of biventricular morphology and function. Since manual post-processing is time-consuming and prone to observer variability, efforts have been directed towards automated volumetric quantification. In this study, we sought to validate the accuracy of a novel approach providing fully automated quantification of biventricular volumes and function in a "real-world" clinical setting. Methods: Three-hundred CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 30 publications
10
58
3
Order By: Relevance
“…There is scarce data on the performance and utility of such algorithms in clinical routine. One recent study investigated a similar algorithm by a different vendor in 300 cases randomly selected cases from routine clinical care [13]. Their study found that agreement between fully automated and expert manual segmentation was lower for the right ventricle than for the left ventricle, lower at 3 T, in cases of compromised image quality and in cases of challenging anatomy such as repaired Tetralogy of Fallot [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is scarce data on the performance and utility of such algorithms in clinical routine. One recent study investigated a similar algorithm by a different vendor in 300 cases randomly selected cases from routine clinical care [13]. Their study found that agreement between fully automated and expert manual segmentation was lower for the right ventricle than for the left ventricle, lower at 3 T, in cases of compromised image quality and in cases of challenging anatomy such as repaired Tetralogy of Fallot [13].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study investigated a similar algorithm by a different vendor in 300 cases randomly selected cases from routine clinical care [13]. Their study found that agreement between fully automated and expert manual segmentation was lower for the right ventricle than for the left ventricle, lower at 3 T, in cases of compromised image quality and in cases of challenging anatomy such as repaired Tetralogy of Fallot [13]. Our study design builds on these results in several aspects: we focused our investigation on the left ventricle and chose to exclude examinations performed at 3 T, examinations with severe artefacts and substantially altered anatomy (severe congenital heart disease, large left ventricular aneurysms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence has proven its significant value in medicine in general, 31 and automated analyses using NeoSoft have already demonstrated excellent reproducibility for cardiac volume quantification compared with manual evaluation as the reference standard. 32 Hence, the extension to strain holds great clinical potential and could finally lead to fully automated clinical-routine GLS quantification with improved management of various diseases. 3,[26][27][28] Nevertheless, absolute agreement comparing FT to tagging or fSENC was less convincing.…”
Section: Agreementmentioning
confidence: 99%
“…The work of Guttman et al (1997) discusses the procedures to be followed while evaluation the cardiac MRI [8]. Backhaus et al (2019) implemented a technique for a computerized quantification of biventricular volumes and function using the cardiac MRI [9]. The work of Khan et al (2016) presented a detailed review of cardiac MRI evaluation procedures discussed in 100 related articles [10].…”
Section: Related Workmentioning
confidence: 99%